2007
DOI: 10.1111/j.1467-8500.2007.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Accountability or Countability? Performance Measurement in the New Zealand Public Service, 1992–2002

Abstract: This article examines how output classes and performance indicators have changed between 1992 and 2002 in five selected departments of the New Zealand Public Service. Process, output and largely artificial service quality performance measures have crowded out outcome, efficiency and effectiveness indicators, across the board. Both output classes and performance indicators have been highly labile, though the reasons for this remain speculative in the meantime. The New Zealand state sector is currently implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…The authors have previously examined performance measurement in the same departments, concentrating on one output class that represented a principal departmental function -for example, species protection for DoC; health and safety for DoL ( Lonti and Gregory 2007 ). In that study the authors found that across the board, performance indicators were highly unstable.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have previously examined performance measurement in the same departments, concentrating on one output class that represented a principal departmental function -for example, species protection for DoC; health and safety for DoL ( Lonti and Gregory 2007 ). In that study the authors found that across the board, performance indicators were highly unstable.…”
Section: Discussionmentioning
confidence: 99%
“…The question of the accountability of the administration towards citizens and politicians is also crucial in a representative democracy. The performance-management system has been dominated by a technocratic and mechanistic logic, but in practice it also has political implications (Johnsen, 2005;and Lonti and Gregory, 2004). Thus there is a need for a more open dialogue between agencies, professionals, managers, political executives, parliament and the general public.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the performance indicators are biased and report on some parts of the operations more than others; moreover, they do not always concentrate on the most vital or important activities of the organization. Stability in the performance indicators over time is also necessary in order to obtain comparable data about the development of performance and provide meaningful benchmarks in the long term (Lonti and Gregory, 2004). 40% of the agencies report that performance indicators have remained stable over the past five years, while the normal situation is that there are some changes in the indicators over time.…”
Section: Performance Indicatorsmentioning
confidence: 99%
“…The contexts of New Zealand and Australia seem to be focused particularly on accountability issues (Barrett, 1997;Chapman and Duncan, 2007;Gregory and Hicks, 1999;Lonti and Gregory, 2007;Mulgan, 2006) and ethical behaviours (Kakabadse et al, 2003;Kinchin, 2007) of public servants. The role of the conflict of interest is also particularly highlighted (Bowman et al, 2001) Even if networked forms of governance are increasing worldwide, the major concern is associated with the overlapping of functions and the shared responsibilities that often characterize the various actors involved in the governance system of PSOs.…”
Section: Discussion and Findingsmentioning
confidence: 99%